2015
DOI: 10.1016/s2213-2600(15)00043-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep-disordered breathing in the general population: the HypnoLaus study

Abstract: Summary Background Sleep-disordered breathing is associated with major morbidity and mortality. However, its prevalence has mainly been selectively studied in populations at risk for sleep-disordered breathing or cardiovascular diseases. Taking into account improvements in recording techniques and new criteria used to define respiratory events, we aimed to assess the prevalence of sleep-disordered breathing and associated clinical features in a large population-based sample. Methods Between Sept 1, 2009, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

56
1,285
13
75

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,997 publications
(1,429 citation statements)
references
References 35 publications
56
1,285
13
75
Order By: Relevance
“…1 Recent population-based studies have shown an alarming increase in the prevalence of OSA, with reported rates of moderate-tosevere OSA (defined as an apnea-hypopnea index (AHI) ≥ 15 events/h) up to 50%. [2][3][4][5] The rise in prevalence is likely due to a combination of factors, such as the obesity epidemic, increased sensitivity of sleep study recording sensors and reduced stringency of scoring criteria as a result of updates. 6,7 The majority of OSA subjects in these studies were previously undiagnosed, suggesting a large burden of sleep apnea subjects that remains unrecognized in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent population-based studies have shown an alarming increase in the prevalence of OSA, with reported rates of moderate-tosevere OSA (defined as an apnea-hypopnea index (AHI) ≥ 15 events/h) up to 50%. [2][3][4][5] The rise in prevalence is likely due to a combination of factors, such as the obesity epidemic, increased sensitivity of sleep study recording sensors and reduced stringency of scoring criteria as a result of updates. 6,7 The majority of OSA subjects in these studies were previously undiagnosed, suggesting a large burden of sleep apnea subjects that remains unrecognized in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnoea (OSA) is a highly prevalent respiratory disorder that affects 6-13% of the general population or more, depending on gender and age group (1,2). OSA is characterized by recurrent episodes of upper airway collapse that result in sleep fragmentation, intermittent hypoxia and the disruption of sleep architecture.…”
Section: Introductionmentioning
confidence: 99%
“…OSA is the most common form of sleep disordered breathing. OSA is common 1 and the reported prevalence has increased in the last two decades 1 with the new data reported mainly in European population of adults 40-85 years old showing that at least mild OSA (apnoea-hypopnoea index ≥5) was present in 84% of men and 61% of women and at least moderate disease (apnoea-hypopnoea index ≥15) was present in 50% of men and 23 % of women 2 . OSA and cardiac disease share some common risk factors and in patients undergoing coronary artery bypass graft (CABG) procedures reported prevalence is high, ranging between 41 and 87% [3][4][5] .High proportions of patients may present for surgery without a previous diagnosis of OSA 6,7 and may be at risk of worse postoperative outcomes 8 .…”
Section: Osa and Cardiovascular Diseasementioning
confidence: 99%